Kualitas Pelayanan Kunjungan Wisata Religi pada Unit Percetakan Al-Qur’an Kementerian Agama RI - Risma Yunita Alfiani; Yulianingsih Yulianingsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study addresses the fluctuation in visitor numbers at the Unit Percetakan Al-Qur’an (UPQ) of the Ministry of Religious Affairs of the Republic of Indonesia, which indicates potential issues in service quality as an educational religious tourism destination. The purpose of this study is to examine the quality of religious tourism services at UPQ based on visitors’ perceptions and experiences. A qualitative descriptive approach was employed to obtain an in-depth understanding of service performance. Data were collected through direct field observations during the Field Work Practice program, semi-structured interviews with institutional supervisors, and analysis of 70 visitor reviews obtained from the official feedback platform provided by UPQ. The data were analyzed through data reduction, categorization, interpretation, and comparison across sources. The findings indicate that the overall service quality at UPQ is perceived as good, particularly in terms of staff empathy, reliability, responsiveness, and assurance. However, the study identifies notable weaknesses in the tangibles dimension, including physical facilities, cleanliness, and supporting infrastructure, which contribute to visitor complaints and affect comfort during visits. These results highlight the importance of continuous improvement in physical facilities and service management to enhance visitor satisfaction and strengthen UPQ’s role as a sustainable educational religious tourism destination.